A Rare Case of Epithelial-Myoepithelial Carcinoma Breast in A Young Female with HER2neu Positivity - Verma, Shipra; Guleria, Bhupesh; Raut, Vrushali; Anand, S; Guleria, Prerna; Tevatia, M S (Annals of Pathology and Laboratory Medicine, 2023)
Epithelial-myoepithelial tumors of breast are biphasic neoplasms, with dual participation of epithelial and myoepithelial components. It is a very rare tumor, common in elderly females. EMC breast resembles its salivary gland counterpart, which itself forms less than 1% of all salivary gland tumors. Herein, we report one such rare case of EMC breast in a young female with aberrant HER2 positivity, a feature not yet reported in literature.